Influence of classification of accounting entities for reporting in the context of legislative changes - Stanley Renáta (Strategic Management, 2017)
Constantly changing accounting legislation brings about the addition of new groups of entities in response to adopted amendment no. 352/2013 Coll. to the Accounting Act with effect from 1.1.2014 by a directive of the European Parliament and of the Council 2012/6/EU has allowed Member States of the European Union to reduce the bureaucratic burden of accounting and preparing financial statements. The largest change in the Accounting Act is introducing a new type of entity 'micro entity'. Classification of accounting entities for small entities and large entities was expanded with effect from 1.1.2015. Each of these accounting entities has special rules for preparing financial statements. To a certain extent the legislation allows the choice of entity classification by size criteria. The right choice has an impact on the processing demands of the financial statements of accounting period 2015 and for the economic decisions of managers and external users in 2016. The aim of the article is to provide overview of the new groups of entities and characterize these entities and the legislation under which the procedure for accounting and reporting is conducted.